La mise en art de la Blackfoot Valley (Montana, USA) ou comment (ré) concilier le front minier et le front écologique ? - Sylvain Guyot; Gabrielle Saumon (Revue de Géographie Alpine)
This article presents a Rocky Mountain valley in the state of Montana (USA), a central symbolic space of the American West that is heavily marked by the identity-charged notions of “wilderness” and “frontier”. With a rich history in mining, logging and ranching benefitting pioneers, the Blackfoot Valley today is an excellent example of the frontline between this extractive history (which is not entirely past) and nature conservation, a genuinely active eco-frontier initiated at the federal, state, local and individual levels. Varying representations and appropriations of mountain areas tend to create socio-economic divisions in the valley’s population. An entirely private, site-specific art project (Blackfoot Pathways: Sculpture in the Wild) creates the possibility of offering an alternative resource to be shared by eco-gentrifiers and a local population adjusting to a post-extractive order, and indeed its site-specific works resonate with both the valley’s mining past and its untamed nature. Does this project mean that there are shared values in this rural space undergoing strong social change? And although it does make it possible to spatially reconcile a mining frontier on its way to heritagisation with a vibrant eco-frontier, will it really help reconcile mountain-dwelling populations with very different socio-economic trajectories over the long term?